Firm Size And Financial Performance On Value Of Banking Companies - Yantri Ulul Azmi; Lilis Setyowati (LPPM ISNJ Bengkalis, 2023)
This research aims to analyze the influence of financial performance on company value in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The data used is secondary data in quantitative form in the form of annual financial reports. The sampling method used purposive sampling, which resulted in a sample of 43 companies. The analytical method used is multiple linear regression analysis. Company size is proxied by SIZE, liquidity is proxied by a loan-to-asset ratio (LAR), profitability is proxied by operating costs and operating income (OCOI), and leverage is proxied by capital adequacy ratio (CAR) as an independent variable, company value is measured using price-to-book value (PBV) as the dependent variable. The results of this research show that company size does not have a significant effect on company value. In contrast, loan-to-asset ratio (LAR), operational costs and operating income (OCOI), and capital adequacy ratio (CAR) positively and significantly affect company value. This research provides practical implications that company value can be used as a measure of the success of company management in future operational prospects to create trust for company shareholders.